The experience and discharge readiness of patients undergoing metabolic and bariatric surgery: a qualitative study - Fang, Shu; Zhang, Cheng; Wei, Meng; Li, Zhen; Chen, Jie; Feng, Bilong; Du, Li (Frontiers in Medicine, 2025)
BackgroundThe discharge readiness for metabolic and bariatric surgery (MBS) patients are designed to facilitate their transition from hospital to home and support early rehabilitation, ultimately improving discharge quality and outcomes.ObjectivesThis study aimed to describe the experiences and discharge readiness of patients undergoing MBS.SettingA Tertiary hospital, China.MethodsAn empirical phenomenological approach was used. Eighteen participants were recruited in Wuhan using convenience sampling. Semi-structured, in-depth, face-to-face interviews were conducted in May 2024. Each interview was transcribed verbatim, and Colaizzi’s method was used to analyze the data.ResultsFive themes emerged from data analysis: post-surgical adaptation and expectations; negative emotions and stigma; knowledge gaps and ongoing education needs; post-discharge self-management and support needs; navigating physical recovery and long-term life planning. Patients faced both physiological and psychological discomfort. Insufficient social support was due to gaps in self-management knowledge and biased perceptions of reintegration. The surgery also impacted their reintegration into society and family life, while the long-term effect encouraged patients to adopt positive coping strategies and seek external support. Family provided primary support, but ongoing professional medical guidance was crucial for successful recovery and reintegration.ConclusionThe discharge readiness of the patient needs to be appreciated and improved. Developing a specific scale to assess readiness for MBS patients are crucial. A multidisciplinary, patient-centered discharge support system, supported by an information platform, should provide real-time, practical guidance for rehabilitation. Furthermore, establishing an effective post-discharge linkage mechanism will enhance self-management and ensure access to appropriate medical and social support.